Good practices for patient safety in the operating room: nurses' recommendations - Larissa de Siqueira Gutierres; José Luís Guedes dos Santos; Caroline Cechinel Peiter; Fernando Henrique Antunes Menegon; Luciara Fabiane Sebold; Alacoque Lorenzini Erdmann
ABSTRACT Objective: To describe nurses' recommendations for good patient safety practices in the operating room. Method: Quantitative, descriptive and exploratory research developed from an online survey of 220 operating room nurses from different regions of Brazil. The data processing for textual analysis was performed by the software IRAMUTEQ. Results: There were eight recommendations: (1) Involvement of the multiprofessional team and the managers of the institution; (2) Establishment of a patient safety culture; (3) Use of the safe surgery checklist; (4) Improvement of interpersonal communication; (5) Expansion of nurses' performance; (6) Adequate availability of physical, material and human resources; (7) Individual search for professional updating; and (8) Development of continuing education actions. Conclusion: These recommendations can be used as care management strategies by nurses for patient safety in the operating room.